Influence of serum leptin levels and Q223R leptin receptor polymorphism on clinical characteristic of patients with rheumatoid arthritis from Western Mexico - Angel-Chávez, Luis Ignacio (2018)
Objective The aim of the present study was to evaluate the possible association between the Q223R Leptin receptor (LEPR) polymorphism (A>G; rs1137101) and leptin levels in patients with rheumatoid arthritis (RA) from Western Mexico. Methods A cross-sectional study was performed with 70 RA patients and 74 controls subject (CS). Disease activity was evaluated using DAS28 score, the Q223R LEPR polymorphism was determined by the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and serum leptin levels, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and rheumatoid factor (RF) were quantified.